EFFORTS TO PRESERVE BANTIK LANGUAGE IN MANADO CITY - Moniung, ilke Janemralina; Tatiana S. Claudia; Dina Ch. M. Rottie (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Indonesia has 718 regional languages. Bantik is one of the regional languages used by people in North Sulawesi. However, the results of expert research show that the Bantik language is in an endangered status. The threat of extinction of a language is a serious problem that needs attention from various parties, including the government, education practitioners, researchers and the user community itself. The rapid development of the era of globalization and modernization threatens the existence of minority languages, including the Bantik language. Then how are the efforts to maintain it to prevent or even solve this problem? The purpose of this study is to identify and explore how the existence of the Bantik language is through the efforts of the user community itself. The data for this study were collected using survey techniques with research instruments in the form of questionnaires, interviews, and direct observation. Data were analyzed qualitatively. The research location at this stage includes 4 sub-districts in the Malalayang area. The results of the study show that the Bantik people in the Malalayang area are concentrated in one community living side by side and still maintaining their culture. But in terms of the use of Bantik language in everyday life, only among the elderly, while among young people and children no longer use Bantik language. The results of observations on the use of Bantik language in groups that are still active show that the use of Bantik language is mixed with Manado Malay. Judging from the structure of society, 85% are Christian, and many religious activities are carried out every day. This can be used as a facility to foster motivation to use Bantik language through these activities. If these potentials are utilized properly, it will be one solution to revive the use of Bantik language.